Does surgical treatment within 4 hours after trauma have an influence on neurological remission in patients with acute spinal cord injury? - Biglari, Bahram; Child, Christopher; Yildirim, Timur Mert; Swing, Tyler; Reitzel, Tim Tobias; Moghaddam-Alvandi, Arash (Therapeutics and clinical risk management, 2016)
Does surgical treatment within 4 hours after trauma have an influence on neurological remission in patients with acute spinal cord injury? Bahram Biglari,1 Christopher Child,2 Timur Mert Yildirim,2 Tyler Swing,2 Tim Reitzel,1 Arash Moghaddam2 1Department of Paraplegiology and Technical Orthopedics, BG Trauma Centre, Ludwigshafen, Germany; 2Heidelberg Trauma Research Group, Center for Orthopedics, Trauma Surgery and Spinal Cord injury, Heidelberg University Hospital, Heidelberg, Germany Background: The proper timing for surgery in patients with acute spinal cord injury is controversial. This study was conducted to detect if there is an advantage in early (within the first 4 hours after trauma) compared to late (between 4 and 24 hours after trauma) surgery on neurological outcome.Methods: In this single institution prospective cohort study, data were analyzed from 51 spinal cord injured patients with an average age of 43.4 (±19.2) years. The influence of early (29 patients within the first 4 hours) as opposed to late (22 patients between 4 and 24 hours) decompression was evaluated by comparing data for neurological outcome. Patients of the study collectively suffered acute spinal fractures from C2 to L3 (cervical 39.2%, thoracic 29.4%, and lumbal 21.6%) or nonosseous lesions (9.8%). American Spinal Injury Association (ASIA) Impairment Scale (AIS) grades were assessed at time of admission and 6 months after trauma or longer depending on the time of release. Surgical treatment included early stabilization and decompression within 24 hours.Results: No significant difference between improved neurological function, measured with the AIS, and an early or late surgery time can be seen (P=0.402). Furthermore, binary logistic regression shows no significant difference between sex or age, and AIS improvement as possible confounders.Conclusion: In our study, all patients with spinal cord injury were treated with spine stabilization and decompression within the first 24 hours after trauma. Surgical decompression within the first 4 hours after trauma was not associated with improved neurological outcome compared to treatment between 4 and 24 hours. In a clinical context, this indicates that there is a time frame of at least 1 day in which optimal care is possible. Keywords: spinal cord injury, surgery, neurological remission, neurological outcome, AIS
Gesehen am 12.05.2020